Level of knowledge in relation to the attitude of medical students about organ donation and transplantation / Lizbeth Aguilar-Andrade, Enrique A. Sanchez-Valdivieso and Virginia G. Chavez-Montes-de-Oca - Aguilar-Andrade, Lizbeth; Sanchez-Valdivieso, Enrique A.; Chavez- (Faculty of Medicine, 2023)
Introduction: Health care provider become a key link in the process of donating organs and tissues for transplantation and influence the perception of society about organ donation. We aimed to measure the level of knowledge in relation to the attitude of medical students about organ donation. Methods: A cross-sectional study was conducted among 102 medical students from year 2 to 4. Results: Sixty six percent were female. Mean (±SD =standard deviation) age of participants was 21.1 ± 2.5395 years. Most of the students barely had enough knowledge; although donation is well accepted by them, there is still a lot of ignorance on the subject, showing fear that organs will be removed before brain death is confirmed, misconceptions about organ trafficking related to ignorance of the legislation, and disagreement with donating the organs of a relative. Conclusions: The need for a continuous and intense education strategy to increase willingness to donate organs and tissues is evident.